Description of a neotype and designation of four lectotypes from Borneo in the genus Curculio (Coleoptera: Curculionidae) - Pelsue, Jr., Frank W. (Zootaxa, 2010)
A neotype is described for Balaninus sellatus Marshall, originally based on a unique female specimen, which will be replaced by a male specimen; and four lectotypes are designated for the following species: B. analis Marshall, B. discreticoxis Marshall, B. imitatior Marshall, and B. quincunx Marshall. All species are now in the genus Curculio Linnaeus. Original type specimens were stolen on the Paris Metro.